Physical activity & health an interactive approach - Kotecki, Jerome Edward (Burlington, MA Jones & Bartlett Learning, 2018)
Physical Activity & Health, Fifth Edition assists and encourage students in developing a personalized physical activity and health plan based on information gleaned from the latest scientific evidence and research. The text uses a distinct interactive approach that instills confidence in students to improve their health and well-being. Through its clear and systematic coverage of the essentials of personal health and fitness, Physical Activity & Health equips students with the information, skills, and practical know-how to gain control of their health.
The physical activity and health connection -- Understanding and enhancing health behaviors -- Principles of physical fitness development -- The heart of physical fitness : cardiorespiratory endurance -- The power of resistance training : strengthening your health -- Focus on flexibility : stretching for better health -- Optimal nutrition for active lifestyle -- Achieving and maintaining a healthy weight -- Achieving optimal bone health -- Mental health and coping with stress -- Making informed decisions about drug use -- Consumer health -- Developing healthy social and intimate relationships -- Protecting your cardiovascular system -- Reducing your cancer risk -- Preventing sexually transmitted infections.
Includes bibliographical references and index.
Keywords: Exercise; Physical fitness; Health